Regional Governance-Stile in Europa. Eine vergleichende Analyse von Steuerungsstilen ausgewählter LEADER-Netzwerke in Extremadura (Spanien), Warmińsko-Mazurskie (Polen) und Western Isles (Schottland) - Ingo Mose; Marta Jacuniak-Suda; Georg Fiedler (Raumforschung und Raumordnung, 2014)
This paper aims at an elaboration of regional governance styles on a wide European scale. Thereby it should help to dissociate from the almost infinite number of diverse contextual interpretations of governance and develop a further perspective towards a deeper analysis and comparison of regional governance phenomena. The results of this paper are based on a comparative case study analysis carried out within the framework of a research project, funded by the German Research Foundation in the years 2008–2011. The research was conducted in selected peripheral rural areas in the EU, namely Extremadura (Spain), Warmińsko-Mazurskie (Poland) and Western Isles (Scotland). The overall objective was to examine the emergence, action orientations, functioning, actor constellations and legitimacy of selected LEADER actor networks.